1975
DOI: 10.1007/bf00614003
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of digoxin from the distal parts of the intestine in man

Abstract: In 12 patients undergoing coloscopy, 0.5 mg digoxin in aqueous alcoholic solution was injected into the transverse colon. The late maximum of the blood level curve at about 2 hours after the administration suggested delayed absorption of the glycoside. However, the 24 hour urinary excretion of 17 +/- 3.4% in 8 patients with normal colonic mucosa demonstrated extensive absorption in the distal part of the bowel. The results have been contrasted with the findings in 4 patients with ulcerative colitis who excrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As drug absorption in rats may vary dramatically between the different segments of the gastrointestinal tract (43), the presence of a second peak indicates a reabsorption phase, attributable to a later absorption of digoxin in the distal parts of the intestine. Digoxin is extensively absorbed in the distal part of the bowel (44), and its absorption in rat small intestine is site-dependent and linked to P-gp activity, which varies all along the intestine (increasing from duodenum to ileum) (45). Western blot studies performed in wild, untreated animals confirmed that P-glycoprotein expression increases from proximal to distal small intestine (46).…”
Section: Discussionmentioning
confidence: 85%
“…As drug absorption in rats may vary dramatically between the different segments of the gastrointestinal tract (43), the presence of a second peak indicates a reabsorption phase, attributable to a later absorption of digoxin in the distal parts of the intestine. Digoxin is extensively absorbed in the distal part of the bowel (44), and its absorption in rat small intestine is site-dependent and linked to P-gp activity, which varies all along the intestine (increasing from duodenum to ileum) (45). Western blot studies performed in wild, untreated animals confirmed that P-glycoprotein expression increases from proximal to distal small intestine (46).…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, the mRNA expression of Abcb1a (Mdr1) and protein expression of P-gp in the upper small intestine were significantly increased in the elemental diet group, and were also increased, though not significantly, in the semi-digested diet group and digested diet group. Digoxin absorption occurs predominantly at the proximal part of the small intestine, [36][37][38][39][40] so changes of Slco (Oatp) family influx transporter and Abc (Mdr) family efflux transporter expression levels at the upper small intestine are most likely to influence digoxin absorption kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Digoxin is absorbed primarily from the small intestine. 10,11 As a class, GI promotility agents can potentially decrease the available intestinal absorption time of concomitantly administered drugs, thereby effecting a reduction in total drug bioavailability. 12,13 For example, previous studies have shown that metoclopramide and cisapride reduce the GI absorption of digoxin, 11,14 an agent with a narrow therapeutic window that is commonly prescribed for congestive heart failure.…”
Section: Journal Of Clinical Pharmacology 2001;41:1131-1139 ©2001 Thmentioning
confidence: 99%